Pengaruh Gaya Kepemimpinan Dan Motivasi Kerja Terhadap Kinerja Karyawan Di PT BGR Logistic Medan - Imam Ahmad Fahreza; Supar Wasesa; Julkarnain (Jurnal Nirta : Inovasi Multidisiplin, 2025)
This study examined three variables: the effect of leadership style on employee performance, the effect of work motivation on employee performance, and the joint effect of leadership style and work motivation on employee performance. This study sought to analyse the influence of leadership style on employee performance and the correlation between leadership style, work motivation, and employee performance. 40 employees engaged in this study. This study employed descriptive analysis and multiple linear regression analysis for data collection. The results demonstrated that employees' leadership style and work motivation both positively and significantly affected their performance, and that the combination of leadership style and work motivation had a positive and significant effect on overall employee performance.